Time series of autonomous phase-sensitive radar (ApRES) measurements at location EIS8 on Ekström Ice Shelf, Antarctica from November 2021 to December 2022 - Ole Zeising; Daniel Steinhage; Sophie Berger; Reinhard Drews; M Reza Ershadi; Tanja Fromm; Tore Hattermann; Frank Pattyn; Olaf Eisen (PANGAEA, 2025)
The dataset consists of raw data from autonomous phase-sensitive radar (ApRES) measurements. The ApRES was operated with two broadband frame antennas at the Ekström Ice Shelf since April 2020 with one measurement every hour. These Lagrangian measurements allow the estimation of basal melt rates based on estimated vertical displacements of englacial and basal reflections. The ApRES is an autonomous operating frequency-modulated continuous wave (FMCW) radar that transmits a tone sweep - called chirp - ranging from 200 to 400 MHz over a period of one second. In order to improve the signal-to-noise ratio, 20 chirps were transmitted within a single measurement. These measurements were repeated every hour. A raw data file contains up to 4 measurements. Background of the pRES-system is published by Nicholls et al. (2015). The processing of the data is described in Zeising et al. (2025).
In: Zeising, O et al. (2025): Time series of autonomous phase-sensitive radar (ApRES) measurements and determined basal melt rates at location EIS8 on Ekström Ice Shelf, Antarctica from November 2021 to December 2022 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.972023